Rice Demand Dynamics in Manggarai Regency, Indonesia: A VECM Approach - Keraru, Ester Nurani; Piran, Ronaldus Don; Bana, Maryance Vivi Murnia; Elo, Alfosus Rodriques (Kadiri University - Faculty of Agriculture, 2026)
Rice is recognized as the principal food commodity for the inhabitants of Manggarai, characterized by high per capita consumption and serving as the main source of energy. This research examined the patterns of rice consumption in Manggarai regency, employing a Vector Error Correction Model (VECM) and utilizing monthly data from 2020 to 2024. The data-gathering process involved coordination with the Department of Agriculture and Food Security, the Department of Trade and Industry, the Population and Civil Registration Office, and the Manggarai Regency Statistics Bureau. Stationary tests confirmed that the variables were integrated of order one, and Johansen cointegration analysis indicated several long-run equilibrium linkages among rice consumption, food prices, population, and ceremonial festivities. The research implies rice consumption is not significantly affected by short-run fluctuations in food prices, population, or cultural factors. Instead, adjustment occurs through the long-run equilibrium mechanism. In the long run, rice consumption is significantly influenced by rice prices, demographic changes, and ceremonial practices: rising rice prices reduce consumption, population growth increases demand, and cultural rituals suppress consumption. These outcomes emphasize the need for policies that stabilize food prices, promote dietary diversification, and integrate demographic and cultural considerations into regional food security strategies.